Dynamic tensile process of blended fabric using finite element method. Issue 5 (9th April 2020) - Su, Xuzhong; Liu, Xinjin
Abstract : Purpose: Tensile property is one basic mechanics performance of the fabric. In general, not only the tensile values of the fabric are needed, but also the dynamic changing process under the tension is also needed. However, the dynamic tensile process cannot be included in the common testing methods by using the instruments after fabric weaving. Design/methodology/approach: By choosing the weft yarn and warp yarn in the fabric as the minimum modeling unit, 1:1 finite element model of the whole woven fabrics was built by using AutoCAD software according to the measured geometric parameters of the fabrics and mechanical parameters of yarns. Then, the fabric dynamic tensile process was simulated by using the ANSYS software. The stress–strain curve along the warp direction and shrinkage rate curve along the weft direction of the fabrics were simulated. Meanwhile, simulation results were verified by comparing to the testing results. Findings: It is shown that there are four stages during the fabric tensile fracture process along the warp direction under the tension. The first stage is fabric elastic deformation. The second stage is fabric yield deformation, and the change rate of stress begins to slow down. The third stage is fiber breaking, and the change of stress fluctuates since the breaking time of the fibers is different. The fourth stage is fabric breaking. Originality/value: In this paper, the dynamic tensile process of blended woven fabrics was studied by using finite element method. Although there are differences between the simulation results and experimental testing results, the overall tendency of simulation results is the same as the experimental testing results.